2018
DOI: 10.5603/kp.a2017.0206
|View full text |Cite
|
Sign up to set email alerts
|

The intracardiac concentrations of the N-terminal-pro B-type natriuretic peptide (NT-proBNP) and the determinants of its secretion in patients with atrial fibrillation

Abstract: A b s t r a c tBackground: N-terminal-pro B-type natriuretic peptide (NT-proBNP) is elevated not only in heart failure (HF) but also in atrial fibrillation (AF). The role and secretion pattern of NT-proBNP in AF is still undetermined. Aim:The study aimed to assess NT-proBNP concentrations in patients with and without preserved left ventricular ejection fraction (LVEF) depending on the type of AF. It was also intended to define the main source of NT-proBNP production within the heart. In addition, it aimed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Our study demonstrated that ARNI can reduce the outcome incidence in HF patients coexisted with atrial fibrillation, it has been reported that atrial fibrillation could increase the serum brain natriuretic peptide, [26] indicating the severity of heart function. The increasing vasoactive peptides strengthen the effect of neprilysin inhibitor.…”
Section: Discussionsupporting
confidence: 54%
“…Our study demonstrated that ARNI can reduce the outcome incidence in HF patients coexisted with atrial fibrillation, it has been reported that atrial fibrillation could increase the serum brain natriuretic peptide, [26] indicating the severity of heart function. The increasing vasoactive peptides strengthen the effect of neprilysin inhibitor.…”
Section: Discussionsupporting
confidence: 54%
“…It has been observed that the patients with insulin resistance had high resistin concentrations and showed to be higher in obese diabetic patients [40]. It has been observed that resistin concentration was shown to be higher in people with heart failure, left ventricular dysfunction, and CVD [41]. According to a recent study, obese patients had significantly higher resistin levels than participants with normal body mass [42].…”
Section: Discussionmentioning
confidence: 99%
“…Admittedly, the inclusion of NT‐proBNP into the scoring algorithm has a potential risk to overestimate the influence of “C” element, congestive HF. However, the prognostic value of NT‐proBNP is independent of heart function in AF patients 9,24,25 . The latent mechanism might be left atrium secretion 26 .…”
Section: Discussionmentioning
confidence: 99%